1987
DOI: 10.1038/327239a0
|View full text |Cite
|
Sign up to set email alerts
|

Scatter factor is a fibroblast-derived modulator of epithelial cell mobility

Abstract: Various factors are known to regulate cell growth and differentiation, but less is known of agents which affect movement and positioning, particularly in epithelial-mesenchymal interactions. Cultured human embryo fibroblasts release a protein with a relative molecular mass (Mr) of approximately 50,000 (50K) that affects epithelial cells by causing a disruption of junctions, an increase in local motility and a scattering of contiguous sheets of cells. To investigate specificity, a range of cells has been examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
785
0
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,256 publications
(806 citation statements)
references
References 0 publications
14
785
0
7
Order By: Relevance
“…Despite its biological relevance, the molecular mechanism responsible for cell migration are still only partially understood. Recent studies had identi®ed actin polymerization and depolymerization as crucial events (Cooper, 1991), and have showed that these processes are regulated by extracellular factors, such as HGF and LPA (Stoker et al, 1987;Hordijk et al, 1994). Although BAG-1 promotes HGF-mediated growth and anti-apoptotic signaling (Bardelli et al, 1996), in our study, no signi®cant di erence among the MKN74 transfectants was observed with regards to migratory responses to HGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its biological relevance, the molecular mechanism responsible for cell migration are still only partially understood. Recent studies had identi®ed actin polymerization and depolymerization as crucial events (Cooper, 1991), and have showed that these processes are regulated by extracellular factors, such as HGF and LPA (Stoker et al, 1987;Hordijk et al, 1994). Although BAG-1 promotes HGF-mediated growth and anti-apoptotic signaling (Bardelli et al, 1996), in our study, no signi®cant di erence among the MKN74 transfectants was observed with regards to migratory responses to HGF.…”
Section: Discussionmentioning
confidence: 99%
“…BAG-1 has been reported to associate with the HGF (scatter factor) receptor, a growth factor receptor which is known to promote cell motility (Stoker et al, 1987), which is sometimes overexpressed in gastric cancers (Di Renzo et al, 1991). To examine the potential role of BAG-1 in promoting cell migration, the MKN74 transfectants were analysed by goldparticle colloid assay with or without FBS or HGF as described previously (Takaoka et al, 1997).…”
Section: Bag-1 Overexpression Promotes Mkn74 Cell Migrationmentioning
confidence: 99%
“…There is some evidence for a pivotal role of HGF in the regulation of the cell motility, and as a mitogen and motogen for certain epithelial cells and vascular endothelial cells in culture (Stoker et al, 1987;Rosen et al, 1990a). HGF prevented loss of cell viability and morphological damage and retarded DNA fragmentation in confluent C2.8 cells (Rovoltella et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that HGF is produced by non-parenchymal hepatic cells including Kupffer cells (Noji et al, 1990), endothelial cells (Stoker et al, 1987;Shima et al, 1991), fibroblasts and fat-storing cells in the liver (Ramadori et al, 1992;Schirmacher et al, 1992), endothelial cells in the lung Yanagita et al, 1992). Experimentally, tumour cells are also known to produce HGF; HGF or mRNA encoding this factor has been detected in fibrosarcoma (Stoker et al, 1987), lung cancer (Yoshinaga et al, 1992;Rygaard et al, 1993;Tsao et al, 1993); hepatoma (Miyazaki et al, 1991) and pancreatic cancer cells (Hirota et al, 1993). Other normal tissues, such as the pancreas, small intestine, thyroid, brain and submaxillary salivary gland are also known to produce HGF (Zarmegar et al, 1990;Wolf et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…This is triggered by extracellular stimuli that regulate the activity of several transcription factors that, in turn, modulate the expression of a number of proteins, ranging from cytoskeletal and cell-cell junctional components to cell cycle regulators and anti-apoptotic effectors 9, 10 . One major environmental inducer of invasive growth is hepatocyte growth factor (HGF, also known as scatter factor), the ligand for the MET tyrosine kinase receptor (also known as the HGF receptor) 11,12,13,14,15,16,17,18,19,20 (Box 1). MET function is required for various morphogenetic events in both embryonic and adult life 21,22 and it drives the malignant progression of several different types of tumours 23 .…”
Section: Introductionmentioning
confidence: 99%